2020
DOI: 10.1080/19490976.2020.1823801
|View full text |Cite
|
Sign up to set email alerts
|

Gut dysbiosis induced by cardiac pressure overload enhances adverse cardiac remodeling in a T cell-dependent manner

Abstract: Despite the existing association of gut dysbiosis and T cell inflammation in heart failure (HF), whether and how gut microbes contribute to T cell immune responses, cardiac fibrosis and dysfunction in HF remains largely unexplored. Our objective was to investigate whether gut dysbiosis is induced by cardiac pressure overload, and its effect in T cell activation, adverse cardiac remodeling, and cardiac dysfunction. We used 16S rRNA sequencing of fecal samples and discovered that cardiac pressure over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(29 citation statements)
references
References 55 publications
2
25
0
Order By: Relevance
“…Intestinal abnormalities caused by HF are gradually being discovered. Previous basic studies revealed that HF animal models exhibited obvious gut dysfunction and intestinal dysbacteriosis (Carrillo-Salinas et al, 2020;Seo et al, 2020). Consistently, Kummen et al (2018) also found that HF patients had decreased microbial richness and altered gut microbiota through profiling 2 independent cohorts.…”
Section: Hf and Intestinal Barrier Dysfunctionsupporting
confidence: 53%
“…Intestinal abnormalities caused by HF are gradually being discovered. Previous basic studies revealed that HF animal models exhibited obvious gut dysfunction and intestinal dysbacteriosis (Carrillo-Salinas et al, 2020;Seo et al, 2020). Consistently, Kummen et al (2018) also found that HF patients had decreased microbial richness and altered gut microbiota through profiling 2 independent cohorts.…”
Section: Hf and Intestinal Barrier Dysfunctionsupporting
confidence: 53%
“…The DI was negatively correlated with two secondary BAs, DCA and LCA (P , 3.4e 213 in both cases; r = 20.62 and 20.75, respectively) (Fig. 6C and D), but positively correlated with UDCA (P = 7.8e 25 , r = 0.36) (Fig. 6E).…”
Section: Resultsmentioning
confidence: 90%
“…Alpha diversity, which describes the number (richness) or distribution (evenness) of different bacterial species in the gut, was greater in the healthy dogs than in dogs with MMVD, but no difference was found among the three MMVD groups. So far, two studies reported reduced alpha diversities in human HF patients and in a rodent model with induced HF ( 24 , 25 ), but other studies showed no change in alpha diversity between HF subjects and healthy controls in humans or dogs ( 20 23 ). We also observed nominal differences in beta diversity, which measures similarity of different microbial groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hematoxylin and eosin (H&E) and picrosirius red staining was performed as previously described ( Ngwenyama et al, 2019 ; Carrillo-Salinas et al, 2020 ). Cardiomyocyte area was determined in H&E stained left ventricle (LV) sections by measuring the area of 10–20 myocytes per heart using ImageJ (NIH; Bethesda, MD).…”
Section: Methodsmentioning
confidence: 99%